Development and validation of a liquid chromatographic-quadrupole time of flight mass spectrometric method for the assay of telmisartan and hydrochlorothiazide in marketed tablet formulations - Vignesh Madhavan, Kowmudi Gullapalli, Anoop Karthika, Ramalingam Peraman, Krishnaveni Nagappan (Journal of Applied Pharmaceutical Science, 2022)
A simple, accurate, rapid, and sensitive method using liquid chromatographic-quadrupole time of flight mass spectrometric method has been developed and validated for the simultaneous estimation of telmisartan (TS) and hydrochlorothiazide (HCTZ) in marketed tablet formulation utilizing olmesartan medoxomil (OSM) as internal standard. Sample preparation employed a simple solvent extraction technique. Chromatographic separation of analytes and internal standard, OSM, has been achieved on a Thermo AccucoreTM C18 column (50 × 4.6 mm i.d, 2.6 µ) using gradient elution with 10 mM ammonium acetate solution and acetonitrile at a flow rate of 0.4–0.6 ml/minute. Mass spectrometric detection was achieved by combined electrospray ionisation as interface in negative polarity mode. Upon MRM ion scan, precursor and product ions were observed at m/z 513.20, 287.11 for TS, m/z 295.94, 204.97 for HCTZ, m/z 557.18, m/z 401.18 for Olmesartan medoxomil, respectively. The method was found to be linear in the range 0.20 to 4.01 ng per injection volume (5 µl) for TS and 0.06 to 1.25 ng per injection volume (5 µl) for HCTZ with precision values (as coefficient of variance)
Keywords: Assay, hydrochlorothiazide, telmisartan, UPLC-QToF, validation